Rapid bioassay to determine the sensitivity of acetolactate synthase (ALS) to inhibitor herbicides (Scientia Agricola, 2001)
In order to compare the acetolactate synthase (ALS) activity of resistant and susceptible biotypes of Bidens pilosa and Amaranthus quitensis to ALS inhibitor herbicides, a method based on ciclopronocarboxilic acid (CPCA) to inhibit the enzyme ketoacidredutoisomerase (KARI) is used. This enzyme catalyzes the reaction after acetolactate in the biosynthesis reaction chain of the aminoacids valine, leucine and isoleucine. In the presence of a KARI inhibitor, carbon from pyruvate flows through the branched chain aminoacid biosynthetic pathway and accumulates in acetolactate, which in the presence of sulfuric acid can be converted to acetoin. The base to distinguish between the resistant and susceptible biotypes is the amount of acetoin formed, which will be much higher in the biotype where the ALS was not inhibited by the herbicide. If acetoin is mixed with naphtol and creatine the solution will develop a reddish color, so that it is possible to quantify indirectly the sensitivity of the ALS to the herbicide by the color of the solution formed. An experiment was carried out with suspected resistant biotypes of Bidens pilosa and Amaranthus quitensis using this method after spraying the plants at the two pair leaf stage with chlorimuron-ethyl and imazethapyr. The ALS of the resistant biotype has insensitivity to ALS inhibitor herbicides.